2014
DOI: 10.20885/eksakta.vol14.iss2.art1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Mg/Al Hydrotalcite by Using Low Supersaturated Precipitation Method With Variation of Mole Ratio

Abstract: This research aims to synthesize Mg/Al hydrotalcite with mole ratio variations of Mg/Al precursor through low supersaturated precipitation method. Mg/Al hydrotalcite was synthesized with Mg/Al mole ratio variation of 1:1, 2:1, 3:1, and 4:1. Mg/Al hydrotalcite was synthesized using NaOH and Na 2 CO 3 base solutions. The mixture of precursor was stirred for 2 hours then treated by hydrothermal at 100 °C for 4 hours. Results of the synthesis Mg/Al hydrotalcite with mole ratio variations is a white powder. The for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The infra-red absorption of 1371 cm -1 was attributed to the symmetry stretching of O=C-O group[42], whereas stretching vibration of Al-O and Mg-O appears on the adjacent peaks of 503 and 449 cm-1 , respectively[37,43]. Septiyaningrum et al[44] reported that the Al-O and Mg-O could observe in distinctly region yet the increase of mole variation of hydrotalcite catalyst, the peak of Mg-O and Al-O are presumably difficult to be identified as shown in Figure2.…”
mentioning
confidence: 99%
“…The infra-red absorption of 1371 cm -1 was attributed to the symmetry stretching of O=C-O group[42], whereas stretching vibration of Al-O and Mg-O appears on the adjacent peaks of 503 and 449 cm-1 , respectively[37,43]. Septiyaningrum et al[44] reported that the Al-O and Mg-O could observe in distinctly region yet the increase of mole variation of hydrotalcite catalyst, the peak of Mg-O and Al-O are presumably difficult to be identified as shown in Figure2.…”
mentioning
confidence: 99%